Examining the Primary School Teachers Views on Teacher Leadership and Political Skills - Hüseyin ASLAN; Temel ÇALIK; Emre ER (Elementary Education Online, 2023)
The purpose of this study was to examine the teachers’ perceptions on teacher leadership and olitic skills. A total of 402 teachers employed in 22 primary schools in Samsun participated in this study. "Teacher Leadership Scale" developed by Beycioğlu and Aslan (2010) and "The Political Skill Inventory in Educational Organizations" developed by Ferris et al. (2005) and were adapted to Turkish by Özdemir and Gören (2015) were used to gather data. Mean, standard deviation, t-test and regression analyses were performed to analyze the data. Results indicated that teachers perceptions on teacher leadership and political skills were high and political skills were significant predictor of teacher leadership.. Results of the study were discussed with respect to improving teacher leadership.